The Influence of Advertising and Brand Ambassadors on Cimory Yogurt Drink Purchase Decisions on Instagram Followers @Cimoryindonesia - Cantika Agustianty Gunanto; Rini Handayani (ORGANIZE: Journal of Economics, Management and Finance, 2023)
This research was conducted on the use of the Instagram application. The purpose of this research is to find out how much influence advertising and brand ambassadors contribute to purchasing decisions, both partially and simultaneously, for followers on Instagram @cimoryindonesia. The research method used in this research is descriptive and associative methods. In this research, the unit of analysis is individuals, namely followers on Instagram @cimoryindonesia. The sample in this study was 100 respondents. Proportional stratified random sampling is the sampling technique used in this research. The analysis method uses multiple linear regression analysis, apart from that, validity and reliability testing of the research instruments is also carried out. Based on the research results, it shows that advertising and brand ambassadors have a partial or simultaneous positive influence on purchasing decisions on Instagram @cimoryindonesia. The influence of advertising on purchasing decisions is 20.3%, while the influence of brand ambassadors on purchasing decisions is 52.1%. The influence of advertising and brand ambassadors on purchasing decisions is 72.4%.